GAYA KOMUNIKASI APARATUR SIPIL NEGARA GENERASI Z DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI JAWA TIMUR - Zahroh Firdaus Taufik; Cucu Hayati (JOURNAL OF ECONOMICS, BUSINESS, MANAGEMENT, ACCOUNTING AND SOCIAL SCIENCES, 2023)
This research aims to analyze the communication style of Generation Z Civil Servants (ASN) within the Department of Labor and Transmigration in East Java Province, focusing on aspects of workplace culture such as decision-making approaches, communication styles, and character traits. This qualitative study adopts a post-positivist paradigm. The findings reveal that the communication style of Generation Z ASN members in the Department of Labor and Transmigration in East Java Province tends to prioritize collaborative decision-making and teamwork over individual work. They prefer to engage in discussions and exchange ideas within their teams, often referred to as "The Relinquishing." These findings reflect the changing dynamics of communication among Generation Z, who place a strong emphasis on open dialogue and mutual support in achieving collective goals. This research provides valuable insights for the management of the Department of Labor and Transmigration in East Java Province to better understand the communication preferences of Generation Z, enabling them to create a more inclusive and effective work environment for these ASN members. Additionally, this study contributes to a deeper understanding of the evolving work culture in the digital age and among younger generations.